Time to sputum culture conversion of Multidrug-Resistant tuberculosis in HIV positive versus HIV negative patients in Lesotho - Louwagie, Goedele M.C. (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.